The «inner» life of the social self: agency, sociality, and reflexivity (Nóema, 2013)
This essay offers a pragmatist portrait of the self, hence, an account starting from the premise that the self is first and foremost an embodied, situated, social actor who possesses the capacity for effective self-criticism. So, in addition to stressing agency, the author emphasizes sociality and reflexivity. Unlike many of the portraits sketched by other pragmatists, however, this one attempts to do fuller justice to the «interior» dimension of human subjectivity. It tries to do so most of all by construing interiority as reflexivity (the relationship of the self to itself).
Keywords: Sociality; agency; reflexivity; interiority (or inwardness); intelligence; pragmatism; Emerson; Darwin; Dewey; Korsgaard